Antimicrobial resistance: a global response - Smith Richard D.; Coast Joanna (The World Health Organization, 2002)
Resistance to antimicrobial therapies reduces the effectiveness of these drugs, leading to increased morbidity, mortality, and health care expenditure. Because globalization increases the vulnerability of any country to diseases occurring in other countries, resistance presents a major threat to global public health, and no country acting on its own can adequately protect the health of its population against it. International collective action is therefore essential. Nevertheless, responsibility for health remains predominantly national. Consequently, there is a potentially significant disparity between the problems and solutions related to antimicrobial resistance and the institutions and mechanisms that are available to deal with them. This paper considers the capacity of national and international institutions and mechanisms to generate a collective response to antimicrobial resistance. Strategies for containing resistance are outlined, with particular reference to globally coordinated activities of countries. The adequacy of national and international responses to resistance is assessed, and the actions that international bodies could take to solve difficulties associated with present responses are highlighted. Approaches are suggested for securing international collective action for the containment of antimicrobial resistance.